2019
DOI: 10.3390/ma12091449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Granite Residue Incorporation on the Behavior of Mortars

Abstract: Civil construction is one of the most resource-consuming sectors in the world. For this reason, the last years have witnessed the study of reusing industrial residues in building materials. The ornamental stone processing industry has a considerable environmental liability related to residue generation during the cutting stages of granite blocks. The objective of this work is to analyze the viability of incorporating granite residues, up to 100%, to substitute sand in coating mortars for building construction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 42 publications
2
25
0
8
Order By: Relevance
“…To make ceramic blocks, a kaolinite clay mass from the city of Campos dos Goytacazes-RJ, Brazil, which presented the same parameters of physical, chemical, and mineralogical characterization, indicated by other researchers who studied the same clay [21][22][23], was used. The ceramic blocks were produced using an Eco Master 7000 Turbo II press, with hydraulic control, 7.5 hp engine, and compression load up to 360 kN.…”
Section: Methodsmentioning
confidence: 99%
“…To make ceramic blocks, a kaolinite clay mass from the city of Campos dos Goytacazes-RJ, Brazil, which presented the same parameters of physical, chemical, and mineralogical characterization, indicated by other researchers who studied the same clay [21][22][23], was used. The ceramic blocks were produced using an Eco Master 7000 Turbo II press, with hydraulic control, 7.5 hp engine, and compression load up to 360 kN.…”
Section: Methodsmentioning
confidence: 99%
“…11 Several studies have already assessed the impact of reusing industrial waste in civil construction materials, one of the best known cases in commercial terms is the blast furnace slag, which went from being a waste to becoming a by-product in the cement industry. 12 Other varied wastes have already been applied to ceramic materials, such as ornamental rock, 13,14 from the pulp and paper industry, 15 cigarettes 16 and others. Most of these studies are limited to questions of technological evaluations of these new materials and are still far from a real large-scale implementation.…”
mentioning
confidence: 99%
“…19 Brazil, as a country that exports a significant amount of ornamental rocks, has to deal with the liabilities generated in terms of the destination of the waste from the cutting and processing of the blocks. 13 Currently, the vast majority of these materials are destined to landfills, although some studies have already pointed out their potential for use in cementitious ceramics. 20 Thus, governments are expected to move forward towards a circularity of the economy for the management of the industrial solid waste, enabling many industries to properly use or dispose their by-products in other production chains.…”
mentioning
confidence: 99%
“…In addition, reference 1 : 1 : 6 mortars (REF116) show lower workability than 1 : 2 : 9 mortars (REF129) due to the comparatively greater amount of cement and minor amount of hydrated lime. is behavior is usually found in mortars and has been reported [20][21][22][23][24]. us, it is found that the composition of mortars directly affects the workability parameters of the material, where mortars with finer particles (such as marble residue) show an increase in workability.…”
Section: Analysis Of Materials Compositionmentioning
confidence: 86%